A semi-quantitative explanation of the cold dwell effect in titanium alloys. (September 2020) - Xi, Guoqiang; Lei, Jiafeng; Qiu, Jianke; Ma, Yingjie; Yang, Rui
Abstract: Cold dwell fatigue has become one critical issue in titanium industry over the past decades. Though some reports have emphasized the importance of time-dependent plastic strain on cold dwell effect in titanium alloys, the mathematical relationship between plastic strain and fatigue life has never been discussed because plastic strain changes continuously no matter in normal cyclic fatigue or dwell fatigue. In this paper, a series of fatigue tests under constant plastic strain is designed to investigate the mathematical relationship between plastic strain and fatigue life in titanium alloys at room temperature in air. Results show that plastic strain has a definitely detrimental effect on fatigue life in titanium alloys. Different from the traditional qualitative mechanisms, one semi-quantitative explanation for cold dwell effect in titanium alloys is proposed by introducing hysteresis energy density. Graphical abstract: Unlabelled Image Highlights: A series of fatigue tests under constant plastic strain is designed. One kind of high throughput fatigue experiment is designed. Plastic strain is verified to play an essential role in cold dwell effect. A semi-quantitative explanation for cold dwell effect in titanium alloys is raised.